The Effect of Pedilanthus tithymaloides (L.) Poit Crude Extract on Wound Healing Stimulation in Mice - Waroonluk Sriwiroch; Narong Chungsamarnyart; Sirirak Chantakru; Pakawadee Pongket; Krisana Saengprapaitip; Urai Pongchairerk (Agriculture and Natural Resources, 2010)
The study aimed to investigate the potential of an ethanolic extract of Pedilanthus tithymaloides to stimulate excision wound healing. Samples of 42 female mice were divided into three groups: group I – methylcellulose (negative control); group II – 0.5% (w/w) crude extract; and group III – 1.5% (w/w) crude extract. The results were compared among treatments and a control group, in terms of wound appearance, parameters of wound healing and a histopathological study. In the treatment groups, the parameters of wound healing were significantly (P < 0.05) higher in comparison with the control group. The histopathological study also showed increased fibroblast, collagen fiber and blood vessel formation. However, the wounds treated by 0.5% crude extract healed faster when compared to the group with 1.5% crude extract. In conclusion, 0.5% crude extract of P.tithymaloides was more suitable for the stimulation of wound healing than 1.5% crude extract because the latter was too concentrated that caused irritation and inflammation, leading to delayed healing.